Factors that Influence Tourist Interest in Kolaka Regency Culinary Tourism Destinations - Usman, Edi; Widya Yusti Handayani; Sagita Trinanda; Irmayanti; Fahmi Syah (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to identify the factors that play a role in influencing tourists' interest in culinary destinations in Kolaka Regency. Research This apply system or approach quantitative. Technique collection data use interview (interview), documentation, observation and questionnaire i(questionnaire). There Were a total of 93 visitors who were sampled in this research, who were part of the tourists visiting culinary destinations in Kolaka Regency who were involved in this research. After that, the information collected was analyzed using the multiple linear regression analysis method. From the results of this research, it is concluded that individually, product and service variables have a significant influence on tourists' interest in culinary destinations in Kolaka Regency. Additionally, simultaneous testingF shows that together these variables significantly influence tourists' interest in culinary tourism in Kolaka